Mesenchymal Stem-Cell Derived Exosome Therapy as a Potential Future Approach for Treatment of Male Infertility Caused by Chlamydia Infection - Izadi, Mahin; Dehghan Marvast, Laleh; Rezvani, Mohammad Ebrahim; Zohrabi, Marzieh; Aliabadi, Ali; Mousavi, Seyed Alireza; Aflatoonian, Behrouz (Frontiers in Microbiology, 2022)
Some microbial sexually transmitted diseases (STDs) have adverse effects on reproductive tract, sperm function and male fertility impairment. Given that STDs are often asymptomatic and cause the major complications such as urogenital inflammation, fibrosis and scarring, optimal treatments should be performed to prevent the noxious effect of STDs on the male fertility. Recently, mesenchymal stem cells (MSCs) derived exosomes have been considered as a new therapeutic medicine due to their immunomodulatory, anti-inflammatory, anti-oxidant and regenerative effects without the consequences through the stem cell transplantation based therapies. Exosome therapy as a noninvasive approach has shown promising results on ability to regenerate damaged sperm and treating asthenozoospermia. Thus the experimental methods may be helpful in the novel treatments of male infertility. Thus, it is demonstrated that exosomes play an important role in preventing the consequences of infection, such as preventing inflammation, reducing cell damage, inhibiting fibrogenesis, and reducing scar formation. This review aimed to overview the studies about the potential therapeutic roles of MSCs-derived exosomes on sperm abnormalities and male infertility caused by STD.